Energy Metabolism and Hyperactivation of Spermatozoa from Three Mouse Species under Capacitating Conditions - Sansegundo, Ester (2022)
Mammalian sperm differ widely in sperm morphology, and several explanations have been presented to account for this diversity. Less is known about variation in sperm physiology and cellular processes that can give sperm cells an advantage when competing to fertilize oocytes. Capacitation of spermatozoa, a process essential for mammalian fertilization, correlates with changes in motility that result in a characteristic swimming pattern known as hyperactivation. Previous studies revealed that sperm motility and velocity depend on the amount of ATP available and, therefore, changes in sperm movement occurring during capacitation and hyperactivation may involve changes in sperm bioenergetics. Here, we examine differences in ATP levels of sperm from three mouse species (genus Mus), differing in sperm competition levels, incubated under non-capacitating and capacitating conditions, to analyse relationships between energetics, capacitation, and swimming patterns. We found that, in general terms, the amount of sperm ATP decreased more rapidly under capacitating conditions. This descent was related to the development of a hyperactivated pattern of movement in two species (M. musculus and M. spicilegus) but not in the other (M. spretus), suggesting that, in the latter, temporal dynamics and energetic demands of capacitation and hyperactivation may be decoupled or that the hyperactivation pattern differs. The decrease in ATP levels during capacitation was steeper in species with higher levels of sperm competition than in those with lower levels. Our results suggest that, during capacitation, sperm consume more ATP than under non-capacitating conditions. This higher ATP consumption may be linked to higher velocity and lateral head displacement, which are associated with hyperactivated motility.